Character and Peacebuilding in Islamic Pedagogy, 'Tazkiyah' and 'Taaruf' Concepts as A Case Study - Qasserras, Mohammed (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study highlights how character and peacebuilding education is manifested within Islamic pedagogy. Islamic pedagogy promotes three crucial aspects to nurture character development: spirit, mind, and body. Its curriculum seeks to cultivate specific areas with the potential to create a healthy generation imbued with critical self-consciousness and critical other consciousness. This study examines two concepts deeply rooted in Islamic education philosophy, namely 'Tazkiyaah' and 'Taaruf', as critical elements shaping individual personality and broad cross-cultural relations. Islamic pedagogy is reenacting human character to contribute to designing a world that fits everyone, regardless of their differences. Islamic pedagogy is a teaching philosophy that focuses on the spirit, mind, body, and space. Spatial awareness is also needed for human beings; 'Taaruf' is the keyword in shaping this type of learning.